Long noncoding RNA DNAJC3‐AS1 promotes osteosarcoma progression via its sense‐cognate gene DNAJC3. (16th January 2019) - Liang, Ridong; Liu, Zezheng; Chen, Zhixu; Yang, Yang; Li, Yuejun; Cui, Zhifei; Chen, Ajuan; Long, Zhenxue; Chen, Jinbin; Lu, Jiachun; Huang, Bin; Li, Qingchu
Abstract: Long noncoding RNAs have been proved to play essential roles in tumor development and progression. In this study, we focused on DNAJC3‐AS1 and investigated its biological function and clinical significance in osteosarcoma. We detected the expression of DNAJC3‐AS1 in 30 pairs of matched osteosarcoma and adjacent nontumorous specimens and osteosarcoma cell lines and analyzed association between DNAJC3‐AS1 levels and clinicopathological factors. We found that DNAJC3‐AS1 expression was up‐regulated in osteosarcoma. High level of DNAJC3‐AS1 was correlated with high differentiated degree ( P  = 0.018) and advanced Enneking stage ( P  = 0.016). Mechanistically, DNAJC3‐AS1 enhanced cell proliferation, migration, and invasion in vitro and in vivo and reduced sensitivity of osteosarcoma to cisplatin. These effects of DNAJC3‐AS1 were reversed by down‐regulation of its sense‐cognate gene DNAJC3. Thus, DNAJC3‐AS1 promotes osteosarcoma development and progression by regulating DNAJC3 and might be a biomarker and therapeutic target for osteosarcoma. Abstract : Long noncoding RNA DNAJC3‐AS1 promotes osteosarcoma development and progression by regulating its sense‐cognate gene DNAJC3 and might be a biomarker and therapeutic target for osteosarcoma.